The Application of Chayote Juice Therapy (Sechium edule) Using the Ida Jean Orlando Nursing Theory Approach to Reduce Blood Pressure in Hypertensive Patients at Simpang Nangka Public Health Center, Rejang Lebong, 2025 - Pratiwi, Intan; Sulastri, Sulastri (Jurnal Kesehatan Mitra Sekawan, 2026)
Hypertension is a disorder of the blood vessels that results in impaired delivery of oxygen and nutrients carried by the blood to body tissues. As a consequence, the heart must work harder to meet these needs, causing an increase in blood pressure with systolic and diastolic levels ≥140/90 mmHg. Among several nursing conceptual models, one of them is Ida Jean Orlando’s theory.The objective of this study is for the researcher to understand and apply Chayote Juice Therapy (Sechium edule) in reducing blood pressure among hypertensive patients through the application of Ida Jean Orlando’s Nursing Theory at the Simpang Nangka Public Health Center working area. The research method used in this study is a case study approach. The respondents consisted of two male patients at Simpang Nangka Public Health Center, Rejang Lebong District. The intervention given to the respondents was Chayote Juice Therapy (Sechium edule), which aimed to reduce blood pressure.The results showed that after the administration of Chayote Juice Therapy (Sechium edule), the respondents experienced a decrease in blood pressure from 178/96 mmHg and 160/100 mmHg to 142/82 mmHg and 130/76 mmHg, respectively.It is expected that the public health center may integrate Chayote Juice Therapy (Sechium edule) as an alternative non-pharmacological therapy for patients with hypertension.